PELATIHAN RISET PASAR DIGITAL DAN VALIDASI IDE BISNIS ONLINE SEBAGAI FONDASI KEWIRAUSAHAAN PADA MAHASISWA BISNIS DIGITAL SEMESTER 2 ISB ATMA LUHUR PANGKALPINANG - Burham Isnanto; Lili Indah; Wishnu Aribowo; Yulianti Yulianti (Bajang Institute, 2026)
Berisi Digital market research competency gaps among early-stage digital business students pose a significant barrier to developing data-driven entrepreneurs. (BPS, 2024) recorded open graduate unemployment at 5.2%, largely attributed to competency mismatches with digital industry demands. This community service activity improved digital market research and online business idea validation competencies among 54 second-semester Digital Business students at ISB Atma Luhur Pangkalpinang through simulation-based pasar data analysis training and lean canvas mentoring. Training was conducted in three workshop sessions (9 hours face-to-face) covering digital market research literacy, pasar data simulation, and lean canvas validation, followed by two weeks of independent mentoring via WhatsApp Group. Evaluation instruments comprised a 20-item pre-post test, portfolio assessment of group business validation reports, and a 9-item Likert 1–5 satisfaction questionnaire. The average pre-test score of 10.1 improved to 16.6 (scale 0–20), a 64.4% increase (p < 0.001, Wilcoxon test). A total of 83.3% of participant groups produced business idea validation reports meeting minimum standards (score ≥70). Average participant satisfaction reached 4.31 on a 1–5 scale (Very Satisfied). All three success indicators were simultaneously achieved, confirming the effectiveness of the three-session simulation-based training design for building foundational digital entrepreneurship competencies among early-semester students at a regional island university in Indonesia